The determinants of bank capital structure - Reint E. Gropp; Florian Heider (European Central Bank (ECB), 2009)
The paper shows that mispriced deposit insurance and capital regulation were of second order importance in determining the capital structure of large U.S. and European banks during 1991 to 2004. Instead, standard cross-sectional determinants of non-financial firms' leverage carry over to banks, except for banks whose capital ratio is close to the regulatory minimum. Consistent with a reduced role of deposit insurance, we document a shift in banks' liability structure away from deposits towards non-deposit liabilities. We find that unobserved time-invariant bank fixed effects are ultimately the most important determinant of banks' capital structures and that banks' leverage converges to bank specific, time invariant targets.
Keywords: G32; G21; 330; bank capital; capital regulation; capital structure; leverage; Bank; Kapitalstruktur; Basler Akkord; Einlagensicherung; EU-Staaten; USA